2009
DOI: 10.2174/1874421400903010004
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Monticellius indicum Mehra, 1939 (Digenea: Spirorchiidae) from the Heart of Green Sea Turtles (Chelonia mydas) in Costa Rica

Abstract: Monticellius indicum Mehra, 1939, is redescribed from the heart of green sea turtles (Chelonia mydas) at Tortuguero National Park, Caribbean coast of Costa Rica. Of the 40 green turtles examined, only 5 (12.5%) were infected with a mean intensity of 1.6. Our specimens are consistent with the original description based on a single fluke from the heart of the same host species in the Arabian Sea, Pakistan, but our redescription provides an unreported range of variation while adding new information about acetabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(9 reference statements)
3
4
0
Order By: Relevance
“…The specimen analyzed had a thin body, with intestinal ceca not fused posteriorly and six irregularly-shaped testes located anterior to the ovary between the external seminal vesicle and the acetabulum; moreover, small spines were found on the acetabulum. These characteristics are in agreement with descriptions of the species using the identifi cation key proposed by Platt (2002) as well as all previous descriptions published on the species (Mehra, 1939;Santoro et al, 2009;. The morphometric analysis and comparison with previously published data on the parasite (Table 1) revealed that the specimen described herein has a larger width of the body, esophagus and ovary, larger length of the external seminal vesicle, larger width of the acetabulum and greater distances between the posterior region of the body and the acetabulum, anterior testicle, external seminal vesicle, ovary and vitelline reservoir.…”
Section: Remarkssupporting
confidence: 91%
See 4 more Smart Citations
“…The specimen analyzed had a thin body, with intestinal ceca not fused posteriorly and six irregularly-shaped testes located anterior to the ovary between the external seminal vesicle and the acetabulum; moreover, small spines were found on the acetabulum. These characteristics are in agreement with descriptions of the species using the identifi cation key proposed by Platt (2002) as well as all previous descriptions published on the species (Mehra, 1939;Santoro et al, 2009;. The morphometric analysis and comparison with previously published data on the parasite (Table 1) revealed that the specimen described herein has a larger width of the body, esophagus and ovary, larger length of the external seminal vesicle, larger width of the acetabulum and greater distances between the posterior region of the body and the acetabulum, anterior testicle, external seminal vesicle, ovary and vitelline reservoir.…”
Section: Remarkssupporting
confidence: 91%
“…Wolke et al (1982) described eggs from the genus Monticellius as type 1, with the following characteristics: "…yellow-brown, elongate and bore two processes, one of which was frequently hooked…" In the present study, only one egg was found in the uterus and exhibited one of the processes terminating in an oval structure (Fig. 1B), which is the same structure described previously by Santoro et al (2009), but not by Mehra (1939), who described M. indicum eggs as "large with narrow, somewhat curved or hook-shaped prolongations at both ends". Considering the redescription performed by Santoro et al (2009) and the present report, we believe that this characteristic could be used in the differential diagnosis of M. indicum eggs.…”
Section: Remarkssupporting
confidence: 86%
See 3 more Smart Citations